Translation of SysML diagram into mathematical Petri net model for quantitative reliability analysis of airbag system. (12th April 2022) - Maurya, Ankur; Kumar, Divya
Airbag systems have become an indispensable safety device to assure the physical welfare of drivers and passengers. Airbag systems are safety-critical systems (SCS) that are developed to avoid catastrophic consequences such as injury, death, or environmental damage. There are numerous methods existing in literature for safety and reliability analysis of airbag systems but these methods are based on pre-assumed transition probability and only suitable for stakeholders having good technical knowledge. The requirement and quantitative reliability analysis of airbag system during design phase are the main goal of this paper. This is done by translating SysML diagram into Petri Net model (PN) and computing non-assumed transition probabilities of the system in real time scenarios. The result has been verified using ASIL ISO 2626 safety standards and compared for different vehicle manufacturers. The most reliable vehicle models are BMW and Chrysler with unreliability of 0.07%.